Properties of Paper : An Introduction - Scott, William E.; Trosset, Stanley; Abbott, James C. (TAPPI, 1995)
After outlining the processes and raw materials of manufacturing paper, details the structural, mechanical, visual, and other properties of different papers; the influence of the environment and its use as a barrier; and the properties required for printing and writing, packaging, and tissue papers.
Keywords: Paper.; elektronické knihy; electronic books